(untitled) (Communicare: Journal for Communication Studies in Africa, 2022)
There seems to be consensus amongst scholars that reputation management rests on a foundationof corporate communication, and it is moreover believed that the chief executive officer (CEO) isthe perceived owner and defender of an organisation’s reputation (Hutton, Goodman, Alexander& Genest, 2001: 248 and Gonring 2004: 12).Since corporate reputation and values instilled through internal corporate communication reverberateoutside organisations (Roberts, 2004), the CEO should utilise internal corporate communicationeffectively to enhance his/her and the company’s reputation among employees as a stakeholder.The research problem that prompted this research has, therefore, been formulated as: Does theinternal corporate communication programme of the CEO of the ABC Group have any significancefor middle management employees’ perception of the reputation of the organisation? The aim ofthe study is to illustrate the link between the internal corporate communication programme of anorganisation's CEO and middle management employees' perception of the reputation of theorganisation.A pragmatic research approach was adopted for this study, and two communication theories – thesystems theory and in particular the interrelatedness aspect thereof, and the flow of informationaspects of the information theory (Bowers & Courtright, 1984: 23) - were used as the conceptualpremise of the study. Based on the fact that the nature of the study is interpretative, a combinedqualitative-quantitative research approach was employed for the collection, analysis and representationof data. The study concurs with the finding that the internal corporate communication programmeof the CEO of the ABC Group does in fact have significance for middle management employees’perception of the reputation of the organisation